2023
DOI: 10.3390/jcm12041429
|View full text |Cite
|
Sign up to set email alerts
|

Metastatic Lung Cancer to the Head and Neck: A Clinico-Pathological Study on 21 Cases with Narrative Review of the Literature

Abstract: Metastases from lung cancer to the oral cavity and to the head and neck generally are very infrequent and usually manifest in advanced stages of the disease. Even more rarely, they are the first sign of an unknown metastatic disease. Nevertheless, their occurrence always represents a challenging situation both for clinicians, in the management of very unusual lesions, and for pathologists, in the recognition of the primary site. We retrospectively studied 21 cases of metastases to the head and neck from lung c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 65 publications
(147 reference statements)
0
2
0
Order By: Relevance
“…Several studies have reported that chronic inflammatory conditions may affect malignant tumor development. 8,18,19 With less clear evidence, claims have been made that the presence of implants can promote cell metastasis and metastatic growth. 8 The peri-implant area is more vulnerable to infection than is the area around natural teeth, which is more likely to remain in a chronic inflammatory condition.…”
Section: Case Reportmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have reported that chronic inflammatory conditions may affect malignant tumor development. 8,18,19 With less clear evidence, claims have been made that the presence of implants can promote cell metastasis and metastatic growth. 8 The peri-implant area is more vulnerable to infection than is the area around natural teeth, which is more likely to remain in a chronic inflammatory condition.…”
Section: Case Reportmentioning
confidence: 99%
“…PET/CT and bone scans can aid the diagnosis, as in this case, a suspicious lesion existed in the oral cavity. 17,19 However, to prevent delays in appropriate treatment, a tissue biopsy must be considered.…”
Section: Case Reportmentioning
confidence: 99%